A Mental Warriors: Health and Socioeconomic Independence Development Program for People with Mental Disorders in Gresik Regency - algristian, hafid; Khamida, Khamida; Fitriyah, Fifi Khoirul; Bariyah, Khadijah Khairul (Universitas Nahdlatul Ulama Surabaya, 2023)
Background: The number of people with mental disorders (ODGJ) in Gresik Regency in 2020 reached 2,250 people with mental health service coverage reaching 64%. These mental health services are limited to examination and treatment only. In the last three years (2020-2022) the Proposing Team initiated a mental and psychosocial recovery program for ODGJ in Tlogopojok Village, Gresik District, and succeeded in achieving a recovery rate from zero to 60%. This activity will continue this year as an ongoing program with a variety of programs and wider sub-district coverage in Gresik District. This community center will be a forum for training, mentoring and coaching activities for ODGJ from both health and socio-economic aspects. Objective: This community service activity aims to develop the health and socioeconomic independence of ODGJ, by establishing a community center for ODGJ. Method: The implementation method used in this Mental Warriors community service activity uses a participatory rural appraisal (PRA) model, namely non-productive communities are invited proactively to build health and socioeconomic independence. The implementation stages start from counseling, training and mentoring. Results: Selecting stable ODGJ can use the PULIH questionnaire, Sensory-Cognitive activities provide provision to ODGJ to understand orders and maintain cleanliness before implementing the culinary program, and culinary training activities for making salted egg dishes can provide provision to ODGJ and their families in the context of independent socio-economic empowerment . Conclusion: 1) Selecting stable ODGJ can still use the PULIH questionnaire, but on the other hand it still requires clinical re-assessment by a mental expert (psychiatrist or psychologist) 2) Sensory-Cognitive activities can provide provisions for ODGJ to understand commands and maintain cleanliness before implementing culinary programs. 3) Culinary training activities for making salted egg dishes and talam cakes can provide provisions for ODGJ and their families in the context of independent socioeconomic empowerment.